Patients experiences on the use of dihydroartemisinin piperaquine as an alternative first line artemisinin-based combination treatment for uncomplicated malaria in Northern Ghana - Chatio, Samuel; Adongo, Philip B.; Dalinjong, Philip A.; Dalaba, Maxwell A.; Beeri, Paula; Akweongo, Patricia; Oduro, Abraham (International Journal of Clinical Trials, 2019)
Background: Three different artemisinin-based combination therapies (ACTs) namely; artesunate-amodiaquine, artemether-lumefantrine and dihydroartemisinin-piperaquine (being the latest to be introduced) are concurrently being used for the treatment of falciparum malaria in Ghana. This study assessed patients’ experience, perceptions and willingness to use dihydroartemisinin-piperaquine, brand name duo-cotecxin as an alternative first line ACT for the treatment of falciparum malaria in Northern Ghana. Methods: This was a qualitative study using phenomenology approach where sixty in-depth interviews were conducted with two groups; thirty patients who were given duo-cotecxin, one group and thirty interviews with patients who were given other ACTs (artesunate-amodiaquine, artemether-lumefantrine) as another group. The interviews were conducted between August and November, 2015 Purposive sampling technique was used to select study participants. The interviews were transcribed and coded into themes using QSR NVivo 11 software for thematic content analysis. Results: All patients who used duo-cotecxin reported that the drug was very good in treating uncomplicated malaria compared to other ACTs they had used in the past. Some of the patients who used other ACTs could not complete their doses because of the side effects. However, none of the patients who used duo-cotecxin reported side effects. The findings revealed high acceptance and preference to use duo-cotecxin to treat uncomplicated malaria compared with other ACTs. All the participants were also willing to recommend duo-cotexcin to their relatives and friends to use. Conclusions: Duo-cotecxin as an alternative first line ACT for treatment of uncomplicated malaria is highly accepted, preferred and there was willingness to use it compared with other first line recommended ACTs.